Evaluation of androgen-induced effects on the uptake of [(18)F]FDG, [(11)C]choline and [(11)C]acetate in an androgen-sensitive and androgen-independent prostate cancer xenograft model - Emonds, Kimy M (Springer, 2013)
BACKGROUND: Androgen deprivation (AD) is generally used as a first-line palliative treatment in prostate cancer (PCa) patients with rising prostate-specific antigen (PSA) after primary therapy. To acquire an accurate detection of tumour viability following AD with positron emission tomography (PET), an androgen-independent uptake of tracers would be advantageous. Several metabolic PET tracers are employed for detecting recurrent PCa. We evaluated the effect of AD on the uptake of 2-deoxy-2-[(18)F]fluoro-d-glucose ([(18)F]FDG), [(11)C]choline and [(11)C]acetate in vivo. METHODS: An [(18)F]FDG, [(11)C]choline and [(11)C]acetate baseline micro(μ)PET/μ computed tomography (CT) scan was subsequently performed in xenografts of androgen-sensitive (LAPC-4) and androgen-independent (22Rv1) tumours in nude mice. An untreated control group was compared to a surgical castration group, i.e. androgen-deprived group. μPET/μCT imaging with the above-mentioned tracers was repeated 5 days after the start of treatment. The percentage change of SUV(max) and SUV(meanTH) in the tumours was calculated. RESULTS: AD did not significantly affect the uptake of [(18)F]FDG and [(11)C]choline in LAPC-4 tumours as compared with the uptake of both tracers in untreated tumours. In control 22Rv1 tumours, [(11)C]choline and [(18)F]FDG uptake increased over time. However, compared with the uptake in control tumours, AD significantly decreased the uptake of [(11)C]choline and tended to decrease [(18)F]FDG uptake. [(11)C]acetate uptake remained unaffected by AD in both PCa xenograft models. CONCLUSIONS: [(18)F]FDG and especially [(11)C]choline PET, which is currently used for the detection of recurrent PCa, could miss or underestimate the presence of local recurrent PCa following AD therapy. [(11)C]acetate uptake occurs independently of androgens and thus may be more favourable for detecting tumour viability during or following AD.